Perineural Spread of Renal Cell Carcinoma: A Case Illustration with a Proposed Anatomic Mechanism and a Review of the Literature - Capek, Stepan; Krauss, William E; Amrami, Kimberly K; Parisi, Joseph E; Spinner, Robert J (World neurosurgery, 2016)
INTRODUCTION: Perineural spread (PNS) is an unusual mechanism of tumor extension and has been typically reported in squamous cell carcinoma, adenocystic carcinoma, and desmoplastic melanoma. Our group has previously demonstrated PNS in rectal, prostate, bladder, and cervical cancer from the primary site along the autonomic nerves to the major somatic nerves and even intradurally. We believe similar principles apply to renal cell carcinoma (RCC) as well, despite the different anatomy. CASE DESCRIPTION: We performed a retrospective search to identify cases of intradural-extramedullary metastases of RCC caused by PNS. Strict anatomic and imaging inclusion criteria were defined: only lesions located between T6 and L3 were included, and PNS as a potential cause had to be supported by imaging evidence. Although 3 cases of spinal intradural metastases were identified, only one met our strict inclusion criteria. A 61-year-old woman developed a late intradural-extramedullary metastasis of RCC 16 years after the original diagnosis that we believe represents an example of visceral organ PNS. CONCLUSIONS: RCC can propagate via PNS from the primary tumor along the autonomic nerves to the aorticorenal, celiac, and mesenteric ganglia and then along the thoracic and lumbar splanchnic nerves to the corresponding spinal nerves and intradurally. We present radiologic evidence together with the review of the literature to support the premise that PNS of RCC not only occurs but goes unrecognized.
Keywords: nádory ledvin; Magnetic Resonance Imaging; Renal cell carcinoma; magnetická rezonanční tomografie; Humans; Metastasis; lidé středního věku; databáze bibliografické; Female; míšní nervy; lidé; ženské pohlaví; Middle Aged; Retrospective Studies; Spinal; Spinal Nerves; karcinom z renálních buněk; nádory míchy; Carcinoma, Renal Cell; retrospektivní studie; Databases, Bibliographic; Spinal Cord Neoplasms; Kidney Neoplasms; Perineural spread